C−H Alkenylation of Pyrroles by Electronically Matching Ligand Control. Issue 17 (5th June 2018) - Kim, Hyun Tae; Lee, Woohyeong; Kim, Eunmin; Joo, Jung Min
Abstract: Directing group and substrate control strategies have frequently been employed for the regioselective C−H alkenylation of acid‐ and oxidant‐sensitive pyrrole heterocycles. We developed an undirected, aerobic strategy for the C−H alkenylation of N ‐alkylpyrroles by ligand control. For C2‐alkenylation of electron‐rich N ‐alkylpyrroles, an electrophilic palladium catalyst derived from Pd(OAc)2 and 4, 5‐diazafluoren‐9‐one (DAF) was used. Alternatively, a combination of Pd(OAc)2 and a mono‐protected amino acid ligand, Ac‐Val‐OH, was useful for C5‐alkenylation of N ‐alkylpyrroles possessing electron‐withdrawing groups at the C2 position. This approach based on the electronic effects of heterocycles and catalysts can rapidly provide a wide range of alkenyl pyrroles from readily available N ‐alkylpyrroles and alkenes. Abstract : In control ! Depending on the electronic character of pyrroles, matching palladium catalytic systems were developed for a regioselective C−H alkenylation. Complementary to directing group and substrate control strategies, this approach based on electronic matching between heterocycles and catalytic systems should be useful for providing a variety of alkenyl pyrroles from readily available N ‐alkylpyrroles and alkenes.